Self-shading in cork oak seedlings: Functional implications in heterogeneous light environments - Esteso-Martínez, Jordán; Peguero-Pina, José Javier; Valladares, Fernando; Morales, Fermín; Gil-Pelegrín, Eustaquio (Acta Oecologica, 2010)
The high self-shading found in Quercus suber seedlings has been interpreted as a feature common for plants growing in high light environments. But many studies reveal that Q. suber has high survival rates under low-light conditions, so a high degree of self-shading could be the consequence of a foliage composed of many small leaves, with no drawbacks for coping with low light. A characterization of the light environment in a Q. suber stand together with a study of photosynthetic parameters of full sunlightexposed (FSLE) and self-shaded (SS) leaves were carried out to tackle this apparent contradiction. Although the number of sunﬂecks longer than 120 min during the 3 months of measurements was low, the occurrence of at least one sunﬂeck longer than 120 min per day in the understory of the forest studied was very common. Sunﬂecks shorter than 30 min promoted an increase in net photosynthesis (A) in FSLE leaves, but not in SS leaves. However, sunﬂecks longer than 60 min led to a very strong decrease in A and in actual photosystem II efﬁciency (FPSII ) in FSLE leaves, when compared to sunﬂecks shorter than 30 min. In SS leaves, changes were, again, negligible. The multi-layered foliage of Q. suber seedlings allowed i) FSLE leaves to obtain the maximum photosynthetic yield for short sunﬂecks, and ii) SS leaves to increase their contribution to the photosynthesis of the whole plant for long sunﬂecks, thus, optimizing the use of light by FSLE and SS leaves during short and long sunﬂecks respectively. Therefore, shoot architecture of Q. suber seedlings involving high levels of self-shading allows to adequately cope with the low but highly heterogeneous light conditions of the understory, particularly when sunﬂecks of contrasting durations take place as it is frequently the case for evergreen Mediterranean forests
The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS
Keywords: Canopy structure; Light stress; Mediterranean; Quercus suber; Self-shading

Differential photosynthetic performance and photoprotection mechanisms of three Mediterranean evergreen oaks under severe drought stress - Javier Peguero-Pina, Jose; Sancho-Knapik, Domingo; Morales, Fermín; Flexas, Jaume; Gil-Pelegrín, Eustaquio (FUNCTIONAL PLANT BIOLOGY, 2009)
The ability of three Mediterranean oaks (Quercus coccifera L., Quercus ilex ssp. ballota (Desf.) Samp and Quercus suber L.) to cope with intense drought was investigated. Water stress reduced stomatal conductance and photosynthesis in these species. Drought-mediated changes in photosynthetic-related parameters allowed the characterisation of the specific photo-protective mechanisms. Specifically, Q. suber downregulated photosynthetic electron transport rates (ETR) closing PSII reaction centres (i.e. decreasing photochemical quenching) and through an antheraxanthin (A) + zeaxanthin (Z)-mediated diminished intrinsic PSII efficiency (Phi(exc.).). These changes were lower in Q. coccifera and Q. ilex ssp. ballota, which decreased further ETR photo-inactivating PSII centres (evidenced by their low predawn F(v)/F(m) ratios at high water stress). The predawn F(v)/F(m) ratio decreased in Q. coccifera largely due to F(m) decreases, whereas in Q. ilex ssp. ballota F(v)/F(m) decreases were due to F(0) increases, below -4 MPa. These F(v)/F(m) decreases were well correlated with increases in the A + Z photo-protective pigments. An analysis of dark respiration and photorespiration as alternative electron sinks under intense drought stress also revealed interspecific differences. The largest imbalance between electrons generated and consumed increased potentially oxidative damage in Q. suber. Subsequently, only Q. suber showed loss of chlorophyll, which is one of the main targets of oxidative damage. Data suggest that Q. coccifera and Q. ilex ssp. ballota seem more able than Q. suber to withstand highly xeric conditions. Therefore, our results question the consideration of Mediterranean evergreen oaks as a homogeneous physiological group.
Keywords: morphological convergence; photoprotection; physiological performance; Quercus; Summer aridity; water stress

ESCLEROFILIZACION DEL PAISAJE MEDITERRÁNEO - Corcuera, Leyre; Morales, Fermín; Gil-Pelegrín, Eustaquio (IV Congreso Forestal Español, 2005)
La encina es una especie con una amplitud bioclimática muy grande ya que aparece en los bioclimas semiáridos, subhúmedos, húmedos y perhúmedos (sensu Ememberg) de la Península Ibérica. En las variantes frías del bioclima húmedo y perhúmedo Quercus ilex ballota compite con los robles deciduos, Quercus faginea y Quercus pyrenaica, ocupando las crestas de las montañas donde las condiciones geopedológicas no son adecuadas para el establecimiento de los robles deciduos. En la región mediterránea el cambio climático global reciente se ha reflejado en un incremento de la aridez y calidez, que tiende a acentuarse en el futuro. A largo plazo, esto podría afectar al funcionamiento y la estructura de los ecosistemas mediterráneos, provocando la sustitución de especies menos resistentes a la sequía o afectando a las poblaciones en localidades subóptimas o en el límite biogeográfico de su distribución. Se estudió el efecto de los dos estreses climáticos propuestos por Mitrakos: el estrés hídrico estival y el estrés por frío invernal en el crecimiento de la esclerófila perennifolia Quercus ilex ballota. Para ello se analizó el efecto de la sequía en el crecimiento primario y secundario de las especies concurrentes Quercus faginea y Quercus ilex ballota y el efecto de las bajas temperaturas y alta insolación en el aparato fotosintético de Quercus ilex ballota en un clima mediterráneo continental.
The following values have no corresponding Zotero field: periodical: IV Congreso Forestal Español pub-location: Zaragoza
Keywords: cambio climático; cambios en el paisaje; carácter perennifolio/caducifolio; competencia interespecífica; Quercus spp

ESCLEROFILIZACION DEL PAISAJE MEDITERRÁNEO - Corcuera, Leyre; Morales, Fermín; Gil-Pelegrín, Eustaquio (IV Congreso Forestal Español, 2005)
La encina es una especie con una amplitud bioclimática muy grande ya que aparece en los bioclimas semiáridos, subhúmedos, húmedos y perhúmedos (sensu Ememberg) de la Península Ibérica. En las variantes frías del bioclima húmedo y perhúmedo Quercus ilex ballota compite con los robles deciduos, Quercus faginea y Quercus pyrenaica, ocupando las crestas de las montañas donde las condiciones geopedológicas no son adecuadas para el establecimiento de los robles deciduos. En la región mediterránea el cambio climático global reciente se ha reflejado en un incremento de la aridez y calidez, que tiende a acentuarse en el futuro. A largo plazo, esto podría afectar al funcionamiento y la estructura de los ecosistemas mediterráneos, provocando la sustitución de especies menos resistentes a la sequía o afectando a las poblaciones en localidades subóptimas o en el límite biogeográfico de su distribución. Se estudió el efecto de los dos estreses climáticos propuestos por Mitrakos: el estrés hídrico estival y el estrés por frío invernal en el crecimiento de la esclerófila perennifolia Quercus ilex ballota. Para ello se analizó el efecto de la sequía en el crecimiento primario y secundario de las especies concurrentes Quercus faginea y Quercus ilex ballota y el efecto de las bajas temperaturas y alta insolación en el aparato fotosintético de Quercus ilex ballota en un clima mediterráneo continental.
Keywords: cambio climático; cambios en el paisaje; carácter perennifolio/caducifolio; competencia interespecífica; Quercus spp